Health Literacy Does Not Explain Patient Portal Use: Results from a Secondary Analysis of a Randomized Controlled Trial. (15th September 2021) - Di Tosto, Gennaro; Walker, Daniel; Sieck, Cynthia; Wallace, Lorraine; MacEwan, Sarah; Gregory, Megan; Scarborough, Seth; Huerta, Timothy; McAlearney, Ann
Abstract : Research Objective: To examine the relationship between health literacy, health numeracy and patient portal use in both the inpatient and the outpatient settings. Study Design: A secondary analysis based on a pragmatic randomized control trial (RCT) conducted among the adult inpatient population of a large US‐based academic medical center (AMC). Patients were provisioned with a tablet providing access to an inpatient portal during their hospital stay and offered the option to sign up to use the AMC outpatient portal. As part of the RCT, study participants were administered two surveys — one during admission, and a second six months post discharge. Log file data tracking use of both patient portals was analyzed and usage statistics were calculated. The admission survey included questions about health literacy and health numeracy, asking patients to interpret medical information. Multivariate regression analysis was used to measure associations between literacy, numeracy, and patient portal use. A mixed‐effects linear model aimed to evaluate whether interaction with the inpatient portal while hospitalized impacted literacy or numeracy as reported in the post‐discharge survey. Population Studied: The studied population was composed of 1538 patients hospitalized between December 2016 and August 2019. The population had an average age of 46 years (sd = 15), was for the majority female (59.7%) and composed mostly of White patients (81.1%). Patients were recruited across the 6 AMC hospitals and their Charlson comorbidity index had an average of 1.6 (sd = 2.1). All the individuals who provided answers to at least one of the six survey items assessing health literacy and numeracy skills were retained for these analyses. Principal Findings: Among the patients in our analytic sample, there were no significant associations with the self‐reported levels of health literacy and numeracy and either frequency of inpatient portal use or number of different inpatient portal functions used. This was generally true also when considering the frequency of outpatient portal use. Additionally, patients post‐discharge actually exhibited lower outpatient portal use frequency despite having reported higher health literacy in the area of dealing with their medical forms (IRR 0.56, 95% CI 0.37 to 0.86). The second assessment of patient skills, conducted through the six‐month post‐discharge survey, did not reveal any difference in their health numeracy; however, there was a significant increase in self‐reported levels of health literacy. Conclusions: Low health literacy and numeracy skills are traditionally considered a barrier to the adoption and use of patient portals. Our study was not able to verify this claim and points towards the necessity to thinking critically about how to promote patients' adoption and use of patient portals in an era when technological access is becoming more widespread. In particular, health numeracy might require more attention to training to enable and sustain patient engagement with the technology. Implications for Policy or Practice: AMCs should develop and deploy targeted efforts to encourage adoption and continued use of patient portals across diverse patient populations. Ultimately, sustained patient portal use could serve as an important strategy in fostering patient‐centered care while serving as a catalyst in reducing health disparities and improving population health. Primary Funding Source: Agency for Healthcare Research and Quality.